Increasing Men's Engagement in HIV Testing and Treatment Programs Through Crowdsourcing: A Mixed-Methods Analysis in Eswatini. Issue 10 (October 2021) - Hlatshwako, Takhona; Conserve, Donaldson; Day, Suzanne; Reynolds, Zahra; Weir, Sharon; Tucker, Joseph D.
Abstract : Background: Sub-Saharan African HIV programs have had limited success in engaging men. Crowdsourcing contests may be a useful method to spur men's engagement in HIV services. We evaluated contributions and social media response to a crowdsourcing contest focused on increasing men's engagement in Eswatini HIV services. Methods: We conducted a crowdsourcing contest to gain insight from the public on how HIV campaigns can more effectively engage young (20–40 years old) men in HIV services. Eligible submissions included images, songs, videos, and Internet memes. We used standard qualitative methods to examine textual themes from submissions. We examined social media response using Facebook analytics, comparing the number of people reached through crowdsourced HIV messages and the number of people reached through conventional HIV messages. Results: We received 144 submissions from 83 participants. They represented 55 towns and all 4 regions of Eswatini. The contest page gained 461 followers on Facebook. Emergent themes included appealing to men's roles as protectors by suggesting that they need to take care of their own health to continue safeguarding their families. Crowdsourced messages reached a mean of 88 individuals across 4 posts; conventional messages reached a mean of 75 individuals across 4 posts. Conclusions: Crowdsourcing contest submissions provided insight on how to encourage men to engage in Eswatini HIV services. Crowdsourcing contests can be effective in collecting messages from men to create more locally relevant communication materials for HIV programs. Abstract : A study of crowdsourcing in Eswatini found that it was an effective method for identifying community messages to encourage men to use HIV services.Supplemental digital content is available in the text.